An autoethnographic spiral: dancing “showerhead” - Waterhouse, Elizabeth (Mimesis Journal, 2024)
This autoethnographic essay considers the duet Duo by choreographer William Forsythe. Autoethnography is practiced through blending ethnographic methodology and dance studies analysis, writing from my critical perspective as a former Forsythe dancer and current dance scholar. My investigation returns to inscriptions and materials gathered during my doctoral fieldwork (2016–2019) to rethink the interrelation of time, memory, and dance in my research onto Duo. My focus is a particular movement of Duo, called showerhead, which I use as a spiralling thread to interweave my arguments and movement analysis. My writing explores how dance historiography may follow practical movement logics, and thereby depart from chronological narratives of rehearsal to performance. Instead, through an autoethnographic spiral, I account for embodied memory that is holistic and nonlinear, articulated relationally and defined by the particularity of Duo’s choreographic labour and curvilinear movements. My longitudinal study of showerhead shows how movement-intensive processes may merge bodies and cross times, as well as challenge insider/outsider dichotomies.